Multifunctional Counting Tablet (MCT) as a teaching tool to learn basic Mathematics among Malaysian primary school pupils / Foo Kien Kheng ... [et al.] - Foo, Kien Kheng; Lim, Keat Heng; Tchong, Fui Mui; Md Razak, Mohamad Idham; Muhamad Hanifah, Muhd Mukhzani; Bong, Sze Sze (2021)
Parents, school administrators and teachers who want to find the best teaching aids for their children or pupils may face the problem of selecting the best teaching and learning tools in particular to manipulatives as they can be expensive. For the learning and teaching of Numbers and Operations in Primary schools, for example there are many to choose. However, having to learn to use and master the uses of the different aids or manipulatives, it does pose a problem for pupils and teachers alike. In addition, there is the cost of multiple purchases and storage of these teaching tools. McT provides the perfect solution to overcome these problems. McT is a multifunctional counting tool i.e., manipulative specially designed for the teaching and learning of Numbers and Operations in Primary schools for Year 1-3 pupils where traditionally these topics require the use of different teaching tools. The feasibility study indicated the McT has its theoretical foundation to be successful as a potential teaching tool to replace some of the presently used manipulatives in the classrooms. In conclusion, the product design process suggested can be considered a possible conceptual framework to run a research to validate McT.